Pengaruh Tata Letak Ruang Kelas Trerhadap Interaksi Siswa dalam Kegiatan Pembelajran - Noviana, Syalza Wahyu; Ichwanto, Muhammad Aris; Sudarto, Sudarto (LPPM Institut Pendidikan Nusantara Global, 2025)
Currently, we still often find messy classrooms, high classroom temperatures, ventilation and lighting systems that are not appropriate for the classroom, tables and chairs that are not neatly arranged, and learning materials that are not arranged well, which affects concentration. and interaction. The aim of this research is to identify the effect of U-Shape and Cluster class divisions on interactions between students and teachers, as well as between students and other students in learning activities, identify the impact on student concentration, and evaluate the effectiveness of the layout. This research uses qualitative methods by means of observation and questionnaires given to class XI students of Modeling Design and Building Information at SMK Negeri 1 Ngasem Kab. Kediri. Data obtained from interviews with students and studying several articles were then processed into narratives for discussion. To assess interaction and concentration in different types of layouts. Research shows that a more flexible layout, namely U-Shape, significantly increases interaction between students and teachers, as well as between students and other students in learning activities. In addition, this research found that ergonomic classroom layouts that can be modified based on learning needs tend to be more effective in increasing student concentration. Thus, classrooms that are designed flexibly and more interactively have proven effective in creating a more dynamic learning atmosphere, increasing engagement, and facilitating student focus. These findings provide recommendations for educators and schools to consider more effective classroom designs to support the teaching and learning process.